DHUHA PRAYER HABITUATION AS A PATHWAY TO SPIRITUAL INTELLIGENCE: A QUALITATIVE STUDY AT A VOCATIONAL HIGH SCHOOL - Sulistia, Nita; Noviriani; Narti, Wiwin (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study investigates the implementation of the Dhuha prayer program at SMK Negeri 3 Bungo, focusing on its operational mechanism, the constraints encountered, and the strategies developed to optimize its impact on students’ spiritual intelligence. A qualitative descriptive design was employed. Data were obtained through participatory observation across forty consecutive prayer sessions, semi-structured interviews with six purposively selected key informants (two vice principals, two Islamic-education teachers, and three students), and documentation of attendance logs and assessment records. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, and credibility was established through source and method triangulation. Findings reveal that the program is delivered through a rotational class schedule, supervision by first-period teachers, and integration with religious-attitude assessment. Observable outcomes include increased discipline, improved emotional stability, and reduced rule violations. Operational constraints concentrate around facility limitations, low intrinsic motivation among students, prayer-hall positioning, and limited mentoring by religiously qualified teachers. The school responded through self-reliant prayer-gear policies, educational sanctions, teacher modeling, and reinforced attendance accountability. The study concludes that Dhuha prayer, when systemically managed, functions as an effective spiritual-habituation mechanism that strengthens spiritual intelligence and supports the affective dimension of vocational education